Mathematical model of Malaria Transmission with Three Optimal Controls Applied to Democratic Republic of the Congo (Global Journal of Science Frontier Research, 2019)
In this paper, we studied the effect of the specific incidence function for the appearance of backward bifurcation in malaria transmission model with standard incidence rate. The stability analysis of disease-free equilibrium (DFE) was investigated, the basic reproduction number R 0 , was obtained using the next generation matrix technique, the existence of the endemic equilibrium was also investigated and the existence of feasible region where the model is wellknown shows that the model exhibits the backward bifurcation phenomenon when R 0 < 1 and the global stability of the endemic equilibrium has been proofed. Further-more, we applied the model to exiting data of the Democratic Republic of the Congo (DRC) to fit some parameters.
Keywords: Stability analysis; standard incidence; simulation; backward bifurcation; optimal control